Can stable isotopes quantify soil carbon build-up from organic fertilizers?. Issue 5 (3rd September 2021) - Jamoteau, Floriane; Balesdent, Jérôme; Basile-Doeslch, Isabelle; Tillard, Emmanuel; Versini, Antoine
ABSTRACT: The application of organic fertilizers (OF) can supply carbon (C) to the soil in crop fields. OF-derived C (OF-C) is often estimated using the differential method that can be biased due to indirect effects of OF on soil C. This study tested three methods to quantify OF–C: (i) the widespread differential method, (ii) the synchronic isotope method comparing plots with and without OF and (iii) the asynchronic isotope method mimicking a trial without a control plot. These methods were implemented on an Arenosol and an Andosol supplied during 13 years with slurry or compost. The results highlighted the relevance of using the synchronic isotope method, which focuses on the direct effect of OFs on the soil organic matter (without bias of vegetation change) and considers control soil's evolution. The higher the isotopic difference between soil and OF, the shorter the method implementation time needed: for an initial difference of 7.5 ‰ and 3.5 ‰, quantification is suitable after 4 and 9 years of fertilization respectively. Attention should be paid to OF-δ 13 C variability to guarantee the method validity. The method proved to be suitable to study the factors controlling the OF-C fate in tropical soils.